18F FDG PET/CT Scan in the Evaluation of Metabolic and Morphologic Change of Breast Cancer after Neoadjuvant Chemotherapy - Ahmed, M Mezbah; Mutsuddy, Pupree; Mandal, Tapati; Nath, Khokon K; Siddique, Abu Bakker; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2023)
Background: Breast cancer remains the most commonly occurring cancer among women across the world and accounts for 69% of cancer deaths. Neoadjuvant chemotherapy (NACT) has been effective in downstaging a primary tumor before surgery. In this study, a fluorine-18, 2-fluoro-2-deoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) scan was used to determine the metabolic and morphological changes of breast cancer after therapy. An 18F-FDG PET/CT scan was done before and after NACT. The change in maximum standard uptake value (SUVmax) ultimately reflects the metabolic status of tumor cells, and the change in tumor diameter represents the morphology of the tumor. Objective: To determine the therapeutic response by assessing metabolic and morphologic changes in breast cancer patients using an 18F-FDG PET/CT scan after NACT. Patients and methods: The study was conducted at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Bangabandhu Sheikh Mujib Medical University (BSMMU) campus, from March 2020 to June 2021, on biopsy-proven female patients diagnosed with breast cancer (stage II to stage IV as defined by the AJCC). A total of nine patients were enrolled in this study. Before and after NACT, a PET/CT scan was performed in accordance with the IAEA CRP guidelines (in a prone posture with breast hanging supported by a breast cushion) and following the NINMAS protocol. Morphological and metabolic data were recorded and analyzed to ascertain the tumor's metabolic and morphologic (as per RECIST 1.1) outcomes. A follow-up 18F-FDG PET/CT after NACT was done using the same dose and the same number of beds (1 minute per bed) as done before NACT. Results: About 89% of patients showed a reduction in tumor size following NACT. The mean tumor size reduction rate was 23.66±22.19 (%) and the difference was statistically significant between prior and after NACT (P < 0.05). Only 11% of patients developed higher SUVmax following NACT. According to RECIST 1.1 criteria, 11.11% of patients had progressive disease, 44.44% had a partial response, and 44.44% were stable. In PET/CT scans, approximately 66.67% of patients responded to NACT. Conclusion: 18F-FDG PET/CT can be used as a potential state-of-the art imaging approach in breast cancer patients before and after NACT. Following NACT, metabolic and morphological changes are visible in the 18F-FDG PET/CT scan, distinguishing responder and non-responder, which must be compared with pathologic response. Bangladesh J. Nuclear Med. 26(1): 13-18, 2023